The relationship between traditional and common Japanese childhood education and adulthood towards avoiding food waste behaviors. (15th May 2022) - Kawasaki, Yui; Akamatsu, Rie; Warschburger, Petra
Highlights: Advising to refrain from leftover was correlated with food waste behaviors. Meal-related rituals was correlated with food waste behaviors. Gratitude for food mediated the association of an advice with food waste behaviors. Gratitude for food mediated the association of rituals with food waste behaviors. Abstract: Japanese parents and educators teach children to refrain from leaving food in their plates. Their teachings have direct (advising children to refrain from leaving food uneaten) and indirect (meal-related rituals before and after mealtimes) influence in enhancing gratitude for food in daily life. This cross-sectional study aimed to examine 1) the interaction of direct and indirect approaches to avoiding food waste behaviors and 2) the mediation of gratitude for food by preventing such behaviors. Overall, 400 Japanese adults (female: n = 200) responded to a self-administrated anonymous questionnaire survey measuring: the present food waste avoiding behaviors; current gratitude for food; direct and indirect childhood approaches for avoiding food waste behaviors. Participants' mean (standard deviation) age and body mass index were 40.0 (11.6) and 21.9 (3.9), respectively. A significant main effect of the indirect approach and the interaction of direct and indirect approaches were obtained by adjusting the participants' background. Moreover, through mediation analyses with percentile-corrected bootstrap confidence intervals, it was observed that gratitude for food mediated the association between direct and indirect childhood approaches and avoiding food waste behaviors. Despite no information on the current meal-related rituals of the respondents, this study suggests the potential of these approaches in enhancing gratitude for food as a new approach to reduce food waste worldwide.